RANCANGAN SISTEM PENDINGIN PANEL SURYA JENIS BOX DENGAN ARAH ALIRAN HORIZONTAL - Azhar Jatmiko; Gaguk Marausna; Ferry Setiawan (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2023)
Based on its geographical location, Indonesia has the potential to use solar energy as a future energy source, considering that Indonesia is located on the equator, which means that Indonesia is always exposed to the sun throughout the year. One of the obstacles in the application of solar power plants is the low efficiency of solar panels and constraints in their storage so that they can be used at night. Seeing the effectiveness of a solar panel working at a temperature of approximately 25˚ C, the solar panel requires cooling by flowing water on the bottom surface to be more efficient. In this study, a solar panel cooling system was made by providing variations in the flow direction of the water medium used. So that it will be known the effect of the cooling system that has been made, starting with the design and installation scheme until testing is carried out to obtain the required variable data. The results obtained in this study were tested for 40 minutes with a time span of every 2 minutes, the temperature of the fluid used in the cooling system was stable, the temperature test increased. In the solar control test, the electricity produced always decreases, in the volt meter test the voltage produced has decreased and the electric current has decreased significantly, the temperature of the solar panel has increased quite high. Therefore, the results of using a device in the form of a solar panel cooling system can be concluded that it is able to slightly reduce the heat on the solar panel but still requires further study.